Secure Web Application Design, Django and Laravel Frameworks - Amel Abdyssalam A Alhaag (Surman Journal of Science and Technology, 2025)
In recent software development, web application security has been an issue of high priority because cyber threats are ever-increasing in both complexity and intensity. This study will compare and contrast the security features and best practices that are provided in two popular web development platforms: Django and Laravel. The paper examines intrinsic security controls, deployment plans and relative efficiency of both frameworks and countering prevalent web weaknesses. This paper will show how developers can take advantage of the inherent security capabilities of these frameworks and apply them in combination with other security measures, by conducting a thorough analysis and using real world examples. The results show that the two frameworks offer powerful security environments, but each of them has particular benefits when applied to a particular security need and development context.